LES DYNAMIQUES POPULAIRESFACE A LA CRISE DE L’EMPLOIEN COTE D’IVOIRE - Robert Gnabro Loba (European Scientific Journal, ESJ, 2012)
Although often ignored by the authorities as well as literature, the popular dynamic response to the crisis of employment is a fact of life in Côte d'Ivoire. Theyare alldone by individualsthangroupswith diverse interests. They derive from thedistrustof local populationvis-à-vis the authorities. Secondly, they are made from the transformation of the image of poverty. Indeed, poverty is now seen not as in evitable but asanegative situation improved. The politicians would benefit, to ensure the successoftheir own actions, tobetter understand these dynamics andtoget them to actin synergywith them.